Investigation of electrical characteristics of fully-depleted SOI device / Zulhelmi Abu Hasan - Abu Hasan, Zulhelmi (2010)
This project is to investigate and to simulate the electrical characteristics of fullydepleted SOI (silicon-on-insulator) and bulk-Si n-MOSFET devices in order to compare their electrical characteristics. The comparisons were focused on three main electrical characteristics that are leakage current, threshold voltage and subthreshold voltage. Two specific channel lengths of the device that had been concentrated are 0.5 and 0.35 micron. All the process and device simulations were done using SILVACO TCAD software. The device structures were constructed using Silvaco-Athena and Atlas-Syntax while the electrical characteristics were examined and simulated using Silvaco-Atlas. Results were analyzed and presented to show that the electrical characteristics of fully-depleted SOI devices are better than bulk-Si devices. It has also shown that the fully-depleted SOI device is superior in the submicron region.